Impact of Boron Acceptors on the TADF Properties of Ortho-Donor-Appended Triarylboron Emitters - Mubarok, Hanif; Lee, Woochan; Lee, Taehwan; Jung, Jaehoon; Yoo, Seunghyup; Lee, Min Hyung (Frontiers in Chemistry, 2020)
We report the impact of boron acceptors on the thermally activated delayed fluorescence (TADF) properties of ortho-donor-appended triarylboron compounds. Different boryl acceptor moieties, such as 9-boraanthryl (1), 10H-phenoxaboryl (2), and dimesitylboryl (BMes2, 3) groups have been introduced into an ortho donor (D)-acceptor (A) backbone structure containing a 9,9-diphenylacridine (DPAC) donor. X-ray crystal diffraction and NMR spectroscopy evidence the presence of steric congestion around the boron atom along with a highly twisted D-A structure. A short contact of 2.906 Å between the N and B atoms, which is indicative of an N->B nonbonding electronic interaction, is observed in the crystal structure of 2. All compounds are highly emissive (PLQYs = 90-99%) and display strong TADF properties in both solution and solid state. The fluorescence bands of cyclic boryl-containing 1 and 2 are substantially blue-shifted compared to that of BMes2-containing 3. In particular, the PL emission bandwidths of 1 and 2 are narrower than that of 3. High-efficiency TADF-OLEDs are realized using 1-3 as emitters. Among them, the devices based on the cyclic boryl emitters exhibit pure blue electroluminescence (EL) and narrower EL bands than the device with 3. Furthermore, the device fabricated with emitter 1 achieves a high external quantum efficiency of 25.8%.